Hirschsprung's disease: the importance of early diagnosis - Aline Franzolli Neumann; Patrícia Picciarelli de Lima; Ana Maria Andrello Gonçalves Pereira de Melo (University of São Paulo, 2013)
Congenital intestinal aganglionosis, also called Hirschsprung disease (HD), is defined as the absence of ganglionic cells in the myenteric (Auerbach) and submucosal (Meissner) plexus, due to a failure in the enteric nervous system development. The extent of intestinal involvement may vary according to the age of embryo development in which this failure occurs. It is not unusual for other malformations to be present, as well as chromosomal trisomies, manly trisomy 21. Enterocolitis is a frequent, life threatening, and feared complication of HD. Moreover, oligohydramnios is a well-known condition frequently associated with malformations, including those related to the gastrointestinal tract. The authors report the case of a newborn that presented a delayed meconium passage. On the third day of life, he presented enterocolitis-the outcome of which was favorable with clinical treatment. While the diagnosis of HD was awaiting confirmation, the enterocolitis relapsed and this time he died due to septic shock. The autopsy findings were compatible with a short segment of congenital intestinal aganglionosis. No other malformation was found. The authors call attention for an early diagnosis of HD whenever the meconium passage does not happen for at least 48 hours and for the risk factors of enterocolitis. This case also demonstrates HD associated with oligohydramnios.